Post-Conflict Democratization: A Comparative Case Study of Cambodia and Nigeriaâ€™s Experiences - Daffa Danendra Cahyadi; Adhi Cahya Fahadayna (KARSA Journal of Social and Islamic Culture, 2025)
Religious conflicts occurred in various countries, from Nigeria's 1980 conflict between Islam and Christianity to Cambodia's religious conflict in 1970. This study examines how religion reconstructs democracy following civil wars in Cambodia and Nigeria. Cambodia emphasizes a spiritual approach for conflict-affected communities to eliminate future conflicts, making religion a collective spiritual tool. Nigeria emphasizes an institutionalized approach using mediation and interfaith dialogue, using religion as socio-political mediation. This comparative study examines religion's role in post-conflict democratic reconstruction in both countries. The research analyzes using Most Similar System Design (MSSD) two countries with systemic similarities, including religious-based civil conflict, influential religious actors, and democracy disruptions between 1970 and 2005. Despite similarities, Cambodia and Nigeria used different faith-based peacebuilding strategies. In Cambodia, Buddhist monk Maha Ghosananda adopted a spiritual approach, focusing on healing through rituals like the â€œPilgrimage of Truthâ€ to restore trust and values for reconstructing democracy. In Nigeria, religious leaders Imam Muhammad Nurayn Ashafa and Pastor James Movel Wuye used an institutionalized approach, emphasizing mediation and interfaith dialogue for socio-political reconciliation. While Cambodia's approach yielded stronger personal reconciliation, Nigeriaâ€™s strategy effectively reduced violence and polarization, establishing deliberative democracy. The study concludes that religious peacebuilding effectiveness depends on context, with the socio-political environment shaping strategies. Quantitative data from V-Dem shows religious actor interventions coincide with improved democratic indicators, highlighting faith-based peacebuildingâ€™s contribution to democratic reconstruction.